Increasing the role of posyandu cadres in toddler teeth development through KMGS card in Karangtengah village, Baturaden district - Fitri Diah Oktadewi; Haris Budi Widodo; Riski Amalia Hidayah; Dwi Nur Indah Sari; Siti Mutia Ayuningtyas (Universitas Muhammadiyah Magelang, 2023)
Dental caries in children is a serious problem that can be caused by a lack of knowledge, attitudes and actions of parents about maintaining oral health. Empowering posyandu cadres is an effort to prevent dental caries in children. One instrument that can be used is the Healthy Teeth Card (KMGS) to monitor the growth and development of children's teeth from 1 to 60 months of age. This service activity aims to increase the role of posyandu cadres as Dental and Oral Health Cadres (KADEGI) in the growth and development of toddler teeth through KMGS in Karangtengah Village, Baturaden District. This community service implementation method begins with simple socialization and training for 29 posyandu cadres. The next stage is the process of assisting posyandu cadres in filling out the KMGS at Posyandu Munthuk and Karangbatur. The result of this programme is a total of 66 toddlers examined by cadres using the KMGS.